Software educativos para el proceso de enseñanza aprendizaje de Matemática en Bachillerato - Agila Mocha, Roberto Jonathan (2025)
The implementation of educational software reinforces the mathematics teaching-learning process and promotes the development of knowledge, skills and competencies in academic preparation. The general objective of the research was to analyze the use of educational software that strengthens the teaching-learning process of Mathematics in high school. It was framed in a mixed approach with descriptive scope, the design of the research was of documentary type in which it was used the documentary, deductive and inductive review method. For the collection of information, it was used the technique of the fiching through instruments such as search logs, bibliographic and content cards, which facilitated the organization of the information and data of the conceptual categories. The results indicate that educational software is implemented in different ways such as: media, resources, tools and didactic strategies. At the same time, it was identified that educational software such as GeoGebra, MATLAB, Desmos and Maple significantly improve the teaching-learning process by facilitating the understanding of complex concepts and encouraging active student interaction. In conclusion, the integration of these media allows to innovate the educational practice, motivate and stimulate the interest of students, improve the understanding of concepts and the development of mathematical and digital skills at the high school level